Developing Techniques for Closed-Loop-Recycling Soda-Lime Glass Fines through Robotic Deposition - Maria Sparre-Petersen; Simona Hnídková (Arts, 2023)
Glass is made from sand—a finite resource. Hence, there is a need to maintain glass in the industrial cycle as described in the Ellen MacArthur Foundation’s circular-economy diagram. This research project examines the reallocation of material resources in the form of waste glass fines from the industrial recycling process for soda-lime glass. According to the plant manager of Reiling Glasrecycling Danmark ApS, the fines are currently sold to be used for insulation. Although this process prolongs the lifespan of the fines before they become landfill waste, a closed-loop circular option would be preferable. In order to establish a closed-loop circular model for waste glass fines, this research investigates their material and aesthetic qualities and proposes a strategy for maintaining the fines in the closed loop cycle together with the soda-lime glass. The fines are manipulated through robotic deposition and formed into 3D geometries. To expand the aesthetic applications for the material, an investigation is conducted by combining 3D geometries with the traditional glassmaking techniques of glassblowing and casting. The research contributes knowledge of the materials’ technical qualities including printability, durability and workability of the 3D prints combined with cast or blown recycled container glass as well as with blown waste glass fines. Technical obstacles are revealed and alternative routes for further explorations are suggested. Finally, the performative and aesthetic qualities of the results are discussed, while artistic applications for recycled soda-lime glass fines remain to be explored in future research.